Integrated mechanisms for QoS and restoration in mesh transport networks - Gong, Ming (My University, 2007)
Survivable networks have the capability to survive from the events of network components failures. The resilience mechanisms in these networks protect and restore the impaired communication paths by using spare capacity. On the other hand, Quality of Service (QoS) mechanisms focus on network capabilities that provide the facilities to differentiate network traffic and offer different levels of service to each class of traffic. Traditionally the survivability algorithms were applied at the physical (optical) layer, whereas the QoS mechanisms mainly applied at packet-forwarding level. Recent technological breakthroughs can now facilitate novel forwarding techniques for optical data bursts that make it possible to capture packets at the optical layer. A major challenge in the transfer of these ultrahigh-speed data bursts is to allocate resources according to QoS specifications and to provide spare capacity required to address link failures.
Keywords: Computer networks (Design Quality control); Telecommunication Traffic; Computer systems (Design Quality control)